Therapeutic equine hyperimmune antibodies with high and broad-spectrum neutralizing activity protect rodents against SARS-CoV-2 infection - Li, Entao; Han, Qiuxue; Bi, Jinhao; Wei, Shimeng; Wang, Shen; Zhang, Ying; Liu, Jun; Feng, Na; Wang, Tiecheng; Wu, Jun; Yang, Songtao; Zhao, Yongkun; et al. (Frontiers in Immunology, 2023)
The emergence of SARS-CoV-2 variants stresses the continued need for broad-spectrum therapeutic antibodies. Several therapeutic monoclonal antibodies or cocktails have been introduced for clinical use. However, unremitting emerging SARS-CoV-2 variants showed reduced neutralizing efficacy by vaccineinduced polyclonal antibodies or therapeutic monoclonal antibodies. In our study, polyclonal antibodies and F(ab’)2 fragments produced after equine were immunized with RBD proteins produced strong affinity. Notably, specific equine IgG and F(ab’)2 have broad and high neutralizing activity against parental virus, all SARS-CoV-2 variants of concern (VOCs), including B.1.1,7, B.1.351, B.1.617.2, P.1, B.1.1.529 and BA.2, and all variants of interest (VOIs) including B.1.429, P.2, B.1.525, P.3, B.1.526, B.1.617.1, C.37 and B.1.621. Although some variants weaken the neutralizing ability of equine IgG and F(ab’)2 fragments, they still exhibited superior neutralization ability against mutants compared to some reported monoclonal antibodies. Furthermore, we tested the pre-exposure and post-exposure protective efficacy of the equine immunoglobulin IgG and F(ab’)2 fragments in lethal mouse and susceptible golden hamster models. Equine immunoglobulin IgG and F(ab’)2 fragments effectively neutralized SARS-CoV-2 in vitro, fully protected BALB/c mice from the lethal challenge, and reduced golden hamster's lung pathological change. Therefore, equine pAbs are an adequate, broad coverage, affordable and scalable potential clinical immunotherapy for COVID-19, particularly for SARS-CoV-2 VOCs or VOIs.